C-HLRD: a category-based hierarchical localisation technique for resource discovery in grid environments. (1st January 2013) - MollaMotalebi, Mahdi; Ismail, Abdul Samad; Ahmed, Aboamama Atahar
Grid resource discovery which is the mechanism of indexing and locating the resources affects significantly the efficiency of grid systems. Some specific characteristics of grid environments such as dynamicity and large-scale make the resource discovery a challenging task. Different approaches for grid resource discovery have been proposed by researchers in recent years. This paper proposes a resource discovery technique highly adapted to large-scale grid environments with the aim of decreasing the message load and response time. It uses a category-based hierarchical structure to index and locate the resources. By this way, the resource query is localised rapidly and efficiently. The indexing structure and processes are implemented in GridSim simulation environment. The results of experiments showed significant decrease in the response time and message load during the search process especially in large scales.